Integrating Local Culture into E-booklet to Strengthen Contextual Learning in Elementary School - Candra Sapta Ramadan; Mahpudin; Yuyun Dwi Haryanti (MIMBAR PGSD Undiksha, 2026)
The rapid advancement of digital education requires instructional materials that are contextual, student-centered, and capable of connecting learning experiences with students’ socio-cultural environments. However, instructional materials used in elementary schools are still predominantly general in nature and provide limited opportunities for students to relate scientific concepts to their local cultural contexts, resulting in less meaningful learning experiences. This study aimed to analyze the need for developing a local culture-based e-booklet as a supplementary instructional material to strengthen contextual learning in Integrated Science and Social Studies (IPAS). The study employed a descriptive quantitative research design involving 22 elementary school teachers and 203 fourth-grade students selected through purposive sampling. Data were collected using four-point Likert-scale questionnaires and analyzed through descriptive statistical techniques using percentage calculations and need-level categorization. The findings revealed a strong demand for the proposed instructional material, with 77.3% of teachers expressing strong agreement and 22.7% agreeing with its development, while 93.1% of students provided positive responses, consisting of 43.8% strongly agreeing and 49.3% agreeing. These findings indicate that integrating local culture into digital instructional materials has considerable potential to support contextual, meaningful, and culturally responsive learning. Therefore, the development of a local culture-based e-booklet is considered essential as a supplementary learning resource that integrates pedagogical, cultural, and digital dimensions to enhance learning quality in elementary education.